Study on Fracture Initiation and Propagation in a Brazilian Disc with a Preexisting Crack by Digital Image Correlation Method - Lin Luo; Xibing Li; Jiadong Qiu; Quanqi Zhu (Advances in Materials Science and Engineering)
The effect of a preexisting crack with different inclination angles and lengths on mechanical properties, fracture initiation, and propagation in a Brazilian disc was investigated in this paper. In the experiment, digital image correlation (DIC) method was employed to record the deformation in the specimen. Different failure patterns, depending on inclination angles and lengths of the preexisting crack, were observed. The fracture initiation position deviates from the tips of the preexisting crack with the inclination angle increasing from 0° to 72° at an interval of 18° per increment. Secondary cracks are more likely to occur in the Brazilian disc with a more inclined and longer preexisting crack. A finite-discrete element combined method ELFEN was used in the numerical investigation to simulate the failure process. This investigation shows that there are good correlations between the experimental and numerical results. Digital image correlation is a good method to obtain the quantitive full-field strain distribution and to observe the strain evolution process in a jointed rock.